Réponses

  • Omnes
  • Modérateur confirmé
2014-04-14T21:12:38+02:00
Salut,


Exercice 1)

a)
-11 + 3x = -5x + 5
3x + 5x = 5 +11
8x = 16
x = 16/8 = 2

b)

5 + 3(2x+2) = 6 - 4(x+1)
5 + 6x + 6 = 6 - 4x - 4
11 + 6x = 2 - 4x
6x + 4x = 2 + 11
10x = 13
x = 13/10 = 1.3

2)

x² = 75
x² - 75 = 0
x² - √75² = 0
(x+√75)(x-√75) = 0
(x+5√3)(x-5√3) = 0

x + 5√3 = 0
x = -5√3
x - 5√3 = 0
x = 5√3

3)
Factoriser A = (6x+7)(2x-5) + (2x-5)(5x+6)
A = (2x-5)|6x + 7 + 5x + 6]
A = (2x-5)(11x + 13)

Bonne soirée !
merci!
tu ne voulais pas la suite du Ex 1 ?
ah, je pensais que tu voulais juste la première question ;)